2017
DOI: 10.1016/j.ymgme.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of mucopolysaccharidosis I mouse brain with two-dimensional polyacrylamide gel electrophoresis

Abstract: Mucopolysaccharidosis type I (MPS I) is due to deficiency of α-L-iduronidase (IDUA) and subsequent storage of undegraded glycosaminoglycans (GAG). The severe form of the disease, known as Hurler syndrome, is characterized by mental retardation and neurodegeneration of unknown etiology. To identify potential biomarkers and unveil the neuropathology mechanism of MPS I disease, two-dimensional polyacrylamide gel electrophoresis (PAGE) and nanoliquid chromatography-tandem mass spectrometry (nanoLC-MS/MS) were appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Importantly, differences between MPS types were also evident, suggesting that particular processes may be disturbed to various extents in different disease types and subtypes, and this inference is supported by different patterns of heatmaps and numbers of significantly changed transcripts ( Figure S2). These results indicate that, apart from a few processes which were reported to be disturbed in some MPS types previously [9][10][11][12][13][14], there are severe cellular changes in a large number of processes which are significantly more pronounced and expanded than expected. In addition, differences between various MPS types appear considerable, pointing to molecular mechanisms of development of different symptoms in the individual diseases from this group that cannot be explained solely on the basis of lysosomal storage of GAG.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Importantly, differences between MPS types were also evident, suggesting that particular processes may be disturbed to various extents in different disease types and subtypes, and this inference is supported by different patterns of heatmaps and numbers of significantly changed transcripts ( Figure S2). These results indicate that, apart from a few processes which were reported to be disturbed in some MPS types previously [9][10][11][12][13][14], there are severe cellular changes in a large number of processes which are significantly more pronounced and expanded than expected. In addition, differences between various MPS types appear considerable, pointing to molecular mechanisms of development of different symptoms in the individual diseases from this group that cannot be explained solely on the basis of lysosomal storage of GAG.…”
Section: Resultsmentioning
confidence: 48%
“…On the other hand, on the basis of the published results, one can conclude that MPS consists of a much broader spectrum of cellular defects than it was supposed previously. Specifically, proteomic and transcriptomic studies on the material isolated from brains of MPS I and MPS VII animal models indicated that expression of genes coding for proteins involved in formation of cytoskeleton and in vacuolar transport is changed relative to wild-type animals [9,10]. Another report indicated that the cell cycle can be impaired in MPS cells, particularly in MPS II [11].…”
Section: Introductionmentioning
confidence: 99%
“…STXBP1, a regulator of synaptic vesicle fusion and docking, was downregulated suggesting impaired synaptic transmission. Notably, alterations in proteins associated with cell death, ubiquitin or inflammation were not detected [13].…”
Section: Proteins Changes Between Samples May Be Found By Comparing 2mentioning
confidence: 98%
“…(a) The 2D silver-stained difference pattern from an MPS 1 brain sample. Spots increased in MPS 1 versus control are outlined in blue; those increased in the control are outlined in red[13]. Spot 1351, MW 78 kDa, which increased by 4.1-fold in the MPS 1 samples was analyzed by LC-MS/MS.…”
mentioning
confidence: 99%
“…Mutations in genes encoding for alpha-tubulin (Tuba1a) and beta-tubulin (Tubb2a, Tubb3, Tubb4a) have been associated with a variety of brain malformations, including different types of cortical phenotypes [48]. As the deregulation of the tubulin isotype, Tubb4b was also found in the brain of MPS I mice [49]; the deregulation of tubulin isoforms Tubb1, Tubb2a, Tubb3, Tubb4a, Tubb5, and Tubb6 found in the MPS IIIB mouse brain strongly suggests that microtubule dysfunction may underlie the pathogenic mechanisms of neurological disorders in specific MPS subtypes.…”
Section: Deregulated Proteins Involved In Cytoskeleton Organizationmentioning
confidence: 99%